Prescribing Patterns for Upper Respiratory Tract Infections: A Prescription-Review of Primary Care Practice in Quetta, Pakistan and the Implications - Hashmi, Hania; Sasoli, Nazeer Ahmad; Sadiq, Abdul; Raziq, Abdul; Batool, Fakhra; Raza, Shanaz; Iqbal, Qaiser; Haider, Sajjad; Umer Jan, Syed; Mengal, Muhammad Alam; Tareen, Abdul Malik; Khalid, Adnan; et al. (Frontiers in Public Health, 2021)
Background: To identify and address potential overuse of antibiotics, it is important to ascertain the prescribing practices of physicians. We therefore conducted this prescription analysis to document URTI-specific antibiotic prescription frequency in a public primary healthcare setting of Quetta city, Pakistan. Methods: A retrospective record review conducted of all prescriptions for URTIs in Combined Military Hospital, Quetta from 1 March to 31st May 2021. The Mann-Whitney U and Jonckheere–Terpstra test was used to evaluate the association between the tendencies of a different group of prescribers. P-value of <0.05 was considered to be of statistical significance. Results: Over the three months, 50,705 prescriptions were screened and analyzed according to the established inclusion and exclusion criteria. A total of 4126 (8.13%) URTI prescriptions met the inclusion criteria, of which 2880 (69.80%) prescriptions contained antibiotics. Among all antibiotics, penicillins (Amoxicillin+Clavulanate) were the most commonly prescribed antibiotic, constituting 1323 (45.9%) of total antibiotics prescribed for all cases, followed by the Macrolide group 527 (18.2%). The Jonckheere–Terpstra test revealed a statistically significant association between the status of the prescriber and the diagnosis (p = 0•002). Furthermore, a moderate positive trend was reported with specialists being more competent in antibiotic prescribing based on their diagnosis, followed by postgraduates and house officers (τ=0•322). Conclusion: The prescribing patterns for the management of URTIs in the hospital were inconsistent with current guidelines. Strict adherence to guidelines must be ensured and antibiotic prescribing for URTIs should be discouraged.